THE EFFECT OF USING BAAMBOOZLE EDUCATIONAL GAMES IN IMPROVING MATHEMATICS LEARNING OUTCOMES OF HIGH SCHOOL STUDENTS - Amalia Maharani; Ria Sudiana; Ilmiyati Rahayu (Universitas Muhammadiyah Metro, 2026)
This research is motivated by the low achievement of students in mathematics even though PBL (Problem Based Learning) has been widely applied. Previous studies have generally placed PBL as a single model, with limited attention to its integration with interactive digital media as well as evaluations that include cognitive and affective aspects. This study develops an approach by integrating PBL and digital competition-based educational games (Baamboozle) which are applied systematically and evaluated through N-gain analysis and student response. The study aimed to compare the mathematics learning outcomes between students taught using Baamboozle-assisted PBL and conventional PBL. The method used was a quasi-experiment with a non-equivalent control group pretest-posttest design at SMAIT Raudhatul Jannah Cilegon, with samples selected through cluster random sampling. Data was collected through pretest, posttest, N-gain analysis, and student response questionnaires. The results showed that the experimental group obtained a higher improvement in learning outcomes than the control group, accompanied by a more positive student response. These findings confirm that the integration of PBL with interactive digital game media is effective in improving learning outcomes as well as student engagement. This research contributes in the form of strengthening gamification-enriched problem-based learning strategies and a more comprehensive evaluation approach in mathematics learning. Penelitian ini dilatarbelakangi oleh rendahnya prestasi siswa dalam matematika meskipun PBL (Problem Based Learning) telah banyak diterapkan. Studi sebelumnya umumnya menempatkan PBL sebagai model tunggal, dengan perhatian terbatas pada integrasinya dengan media digital interaktif serta evaluasi yang mencakup aspek kognitif dan afektif. Penelitian ini mengembangkan pendekatan dengan mengintegrasikan PBL dan game edukasi berbasis kompetisi digital (Baamboozle) yang diterapkan secara sistematis serta dievaluasi melalui analisis N-gain dan respons siswa. Penelitian bertujuan membandingkan hasil belajar matematika antara siswa yang diajar menggunakan PBL berbantuan Baamboozle dan PBL konvensional. Metode yang digunakan adalah kuasi-eksperimen dengan desain non-equivalent control group pretest-posttest di SMAIT Raudhatul Jannah Cilegon, dengan sampel yang dipilih melalui cluster random sampling. Data dikumpulkan melalui pretest, posttest, analisis N-gain, dan angket respons siswa. Hasil penelitian menunjukkan bahwa kelompok eksperimen memperoleh peningkatan hasil belajar yang lebih tinggi dibandingkan kelompok kontrol, disertai respons siswa yang lebih positif. Temuan ini menegaskan bahwa integrasi PBL dengan media game digital interaktif efektif dalam meningkatkan hasil belajar sekaligus keterlibatan siswa. Penelitian ini memberikan kontribusi berupa penguatan strategi pembelajaran berbasis masalah yang diperkaya gamifikasi serta pendekatan evaluasi yang lebih komprehensif dalam pembelajaran matematika.